Comparison of SPECT/CT, AEEG, and 3D-pCASL in people with epilepsy - Rong Chen; Qing Zhang; Yajun Li; Jingyun Chen; Xu Wang; Yanzi Jin; Fang Li; Qiuyan Chen; Mengyun Li (Frontiers in Neurology)
ObjectiveTo analyze the clinical value of single-photon emission computed tomography (SPECT)/computed tomography (CT), ambulatory electroencephalogram (AEEG) and three-dimensional pseudo-continuous arterial spin labeling (3D-pCASL) in people with epilepsy (PWE).MethodsThe study included 98 PWE who were treated in The General Hospital of Ningxia Medical University from December 2021 to September 2023. The positive detection rates and characteristics of SPECT/CT, AEEG and 3D-pCASL were compared. Additionally, the agreement between SPECT/CT, 3D-pCASL and AEEG-positive results was analyzed.ResultsThe positive detection rates for SPECT/CT, AEEG, and 3D-pCASL examinations were 77.55% (76/98), 62.24% (61/98), and 54.08% (53/98) respectively. SPECT/CT exhibited higher positive detection rates than AEEG (aOR = 1.165, 95%CI: 1.036–1.311, p = 0.011) and 3D-pCASL (aOR = 1.265, 95%CI: 1.119–1.430, p < 0.001), no significant difference was observed between AEEG and 3D-pCASL (aOR = 0.922, 95%CI: 0.810–1.048, p = 0.213). In combined modalities, the positive detection rate of AEEG+SPECT/CT + 3D-pCASL (93.88%, 92/98) was higher than AEEG+3D-pCASL (79.59%, 78/98, p = 0.003), but showed no statistically significant difference compared to AEEG+SPECT/CT (88.78%, 87/98, p = 0.204). The proportions of PWE with no lesions, focal lesions, unilateral multifocal lesions and bilateral lesions across the three modalities results revealed statistically significant differences (p < 0.05). Among 61 PWE with interictal epileptiform discharges (IEDs) detected by AEEG, the agreement rate between SPECT/CT and AEEG was 63.93% (39/61), while that of 3D-pCASL was 39.34%(24/61), the difference is statistically significant (p = 0.007). In PWE with AEEG-detected temporal lobe (43 cases) and frontal lobe (31 cases) IEDs, SPECT/CT exhibited higher agreement rate with AEEG compared to 3D-pCASL (p < 0.05).ConclusionSPECT/CT demonstrated a high positive detection rate and showed strong agreement with AEEG-positive results in PWE. The combined use of SPECT/CT, AEEG and 3D-pCASL significantly increased the positive detection rate. These findings highlight the advantages of SPECT/CT and combined modalities.